A Verification and Evaluation Method for Top-down Design of Sprag Clutches - Yu Hao; Lu Min; Chen Liqiang; Li Zhengminqing (Jixie chuandong)
A verification and evaluation method for the top-down design of sprag clutches is proposed for the prediction of the clutch performance. The research targets are associated with sprag, inner and outer shafts, so four mathematic verification models are derived from von Mises stress, contact stress, gripping angle, and percent of sprag rise, which are refined from the comprehensive performance. Taking the clutch of model J8331 as an example, the feasibility of the method and strategy proposed in this study is compared and verified through theoretical analysis and finite element simulation. Based on this, a dynamic law of nonlinear positive correlation between load and the above indicators is obtained.